FABRICATION OF GUARDIAN LAWN INTEGRATED AI-POWERED SMART LAWN MOWING AND HOME SECURITY - BONELA VAMSI; SANKA SATYA SAI; KAMBALA SATEESH KUMAR; BUGATHA MAHESH; 5ANNEPU LAXMANA PRASAD; 6BOKKELA ABHISHEK; Dr. M. SRINIVASA RAO (The Bioscan, 2024)
The GUARDIAN LAWN project introduces a multifunctional robot for autonomous lawn care and enhanced home security. This initiative emphasizes the creation of a robust chassis that can navigate various terrains, a sophisticated suspension system, and a customizable grass-cutting mechanism. A notable feature of this robot is its vacuum system, which efficiently collects cut grass into a sump tank, keeping the lawn tidy and well-maintained. The construction process involves several tasks such as welding, cutting, and assembling components to build a durable structure capable of withstanding different environmental conditions. The robot has advanced electronics, including an Intel RealSense LiDAR for boundary detection. It is controlled by an Arduino Mega, enabling it to navigate and mow autonomously within set boundaries. Additionally, the GUARDIAN LAWN robot features a night-time security mode, using an onboard camera to monitor its surroundings and send alerts in case of unauthorized access. With the ability to operate in manual, semimanual, and automatic modes, the robot can seamlessly transition between lawn maintenance and security tasks, offering a versatile solution that combines advanced fabrication with smart automation technologies.